Socialization Related to the Dangers of Kites, Laser Beams, Hot Air Balloons, and Drones Around Silampari Lubuklinggau Airport - Febiyanti, Herlina; Yuniar, Dwi Candra; Oka, I Gusti Agung Ayu Mas; Putra, Bambang Wijaya; Munir, M Syahrul; Rizaldi, Ricky; Khatami, Muhammad Ali; Amalia, Aisyah Piranti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The implementation of socialization in the Tridharma of Higher Education framework is by conducting research and compiling Scientific Journals within the Palembang Aviation Polytechnic, South Sumatra. In addition, this activity aims to increase the knowledge and awareness of the general public around the Silampari – Lubuklinggau Class III Airport Operator Unit. This activity also informs about the dangers of kites, laser beams, hot air balloons, and drones around the air space in Silampari – Lubuklinggau as well as the safe distance of building construction, especially in the Flight Operation Safety Area, especially people who live close to the Flight Operation Safety Area (KKOP). The method used for socialization is a participatory Focus Group Discussion (FGD) by resource persons and discussions with communities living around the Silampari – Lubuklinggau Class III Airport Operator Unit that the results are expected so that participants know the results of socialization related to activities that can endanger flights. Then, the results of the socialization were published on the social media of the Palembang Poltekbang.